Financial stress during COVID-19: implications for parenting behaviour and child well-being. Issue 1 (8th September 2022) - McGill, Megan G; Purkey, Eva; Davison, Colleen M; Watson, Autumn; Bayoumi, Imaan
Abstract : Background: Family financial stress and parenting behaviours are each associated with child behaviours. We sought to explore the association between parent financial stress and child socioemotional and behavioural difficulties during the COVID-19 pandemic and examine parenting behaviour, including overreactive and lax parenting approaches, as a potential mediator to this relationship. Methods: Cross-sectional sample of parent and child data pairings in Ontario, Canada between April and November of 2020. Linear models were used to describe the relationships between financial worry, child Strengths and Difficulties Questionnaire (SDQ) total difficulties and parenting behaviours measured by the Parenting Scale 8-item (PS-8), which includes measures of both overreactive and lax parenting tendencies. Formal mediation testing was performed to assess the potential mediating role of parenting behaviour. Results: 528 parent and child pairs were enrolled from largely European ancestry (78%), female (93%) and varied household income levels. Analysis revealed increased financial worry during the COVID-19 pandemic was significantly associated with increased child SDQ total difficulties scores (β=0.23, SE=0.10, p=0.03). This relationship was mediated by reported parenting behaviour, independent of parent education, household income, parent age, parent sex, parent anxiety and child sex (total effect: β=0.69, p=0.02, average causal mediation effects: β=0.50, p=0.02, average direct effects: β=0.19, p=0.08). Conclusion: Financial stress during the COVID-19 pandemic was associated with poorer child social and emotional well-being. Parenting behaviours measured by the PS-8 significantly mediated these effects. This work supports the importance of policies aimed to alleviate family financial stresses and highlights the potential impact such policies have on child well-being.